Social Status Of Women In Kashmir Valley - Shabir Ahmad Lone; Dr. E. Ravi (PT. Radja Intercontinental Publishing, 2026)
Life patterns in Kashmir, particularly women's cosmologies, have been shaped by geopolitical, historical, religious, and socioeconomic influences. Women have endured a torturous, protracted journey through many phases, experiencing a range of highs and lows. Women are exalted in historical accounts that date all the way back to the 13th century A.D. In ancient periods, several queens served as independent sovereigns, queen-regents, or military leaders. However, a detailed examination of these narratives reveals the inherent prejudices and discrimination against women in the prehistoric social system. There is no way to defend them or even consider them honourable. This paper makes a modest attempt to examine the social status of women in the past as well as in the present .In the past, women were treated with decency and respect. During this time, there were female rishis who were well-respected. In royal homes, women were respected and had a significant influence on administrative and decision-making processes. They had a solid education across the board and were active in politics. There is no indication of women being hidden or covered up in Kashmir, and she goes around freely, mirroring the glittering, free-flowing waters of her nation's springs. By this period, women had transitioned from the domestic to the political sphere .in the present era women are showing remarkable performance in every aspect and are contributing very much towards the development of the society.